(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The polity of our country has realized the significanceof the development of weaker sections specially the scheduled castes sinceIndependence. Consequently, planned efforts have been made for their upliftmentby the government. This paper has examined the progress made with regard totheir social (health, housing, workforce participation, availability of basicamenities and wage employment under income generation schemes), educational andoccupational status. Based on secondary data, it has been found that no doubt,a positive change on various socio-economic parameters has been recorded but,that change has touched merely less than half of their population. Further, thegap between the mainstream and scheduled caste population still persistssignificantly in our traditional society. Therefore, there is an urgent need toreorient and focus the strategy in order to support the lesser privileged byproviding qualitative education and infusing among them the individualistic andmoralistic values of self-denial, temperance, forethought, thrift, sobriety andself-reliance essential to bring these downtrodden into the nationalmainstream. With the noble intention of self-employment, resulting inreducing the unemployment and poverty among the backward classes, government ofMaharashtra established Backward ClassDevelopment Corporation Ltd., in the year 1978, recently the above institutioncompleted 30 years of its services. The social strata which is known as thebackward class represents the down trodden classes of the society. BC has itsorigin in the ancient Indian social system. The ancient Indian social systemsdivides the society into four broad classes namely the Brahmin, the warriorclass, the serving class in addition to this fifth class known as who wereuntouchable existed in ancient India. With a view of socialistic pattern ofsociety as mentioned in the constitution of India along with the basicprinciples of equity, fraternity, freedom and justice for all Government atCentral and State levels established corporations which meant to work as agentsof economic development of the backward classes by providing finance to them.corporations are playing very dominant role for the development of backwardclasses by providing finance and creating self-employment opportunities for thebackward classes.